2023
DOI: 10.3390/pathogens12020255
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis after Transcatheter Aortic Valve Replacement: Challenges in the Diagnosis and Management

Abstract: Although initially conceived for high-risk patients who are ineligible for surgical aortic valve replacement (SAVR), transcatheter aortic valve replacement (TAVR) is now recommended in a wider spectrum of indications, including among young patients. However, similar to SAVR, TAVR is also associated with a risk of infectious complications, namely, prosthetic valve endocarditis (PVE). As the number of performed TAVR procedures increases, and despite the low incidence of PVE post-TAVR, clinicians should be famili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
0
0
0
Order By: Relevance
“…12 Since TAVR was first developed and reported in 2002, 13 there have been numerous studies reviewing TAVR-PVE but very few reported cases of TAVR-PVE due to P. aeruginosa. [2][3][4][5][6][7][8][9][10] The most common microorganisms causing TAVR-PVE have consistently been Enterococcus species, coagulase-negative Staphylococcus species, S. aureus, and Streptococcus species. Aerobic gram-negative bacilli causing TAVR-PVE are unusual, and P. aeruginosa endocarditis is rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Since TAVR was first developed and reported in 2002, 13 there have been numerous studies reviewing TAVR-PVE but very few reported cases of TAVR-PVE due to P. aeruginosa. [2][3][4][5][6][7][8][9][10] The most common microorganisms causing TAVR-PVE have consistently been Enterococcus species, coagulase-negative Staphylococcus species, S. aureus, and Streptococcus species. Aerobic gram-negative bacilli causing TAVR-PVE are unusual, and P. aeruginosa endocarditis is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of infective endocarditis after transcatheter aortic valve replacement (TAVR)/transcatheter aortic valve implantation (TAVI) ranges from 0.67% to 3.53% 1 . The most common microbes causing TAVR-associated prosthetic valve endocarditis (TAVR-PVE) are Enterococcus species, coagulase-negative Staphylococcus species, S. aureus , and streptococcal species 2–10 . Aerobic gram-negative bacilli are distinctly uncommon causes, and TAVR-PVE due to Pseudomonas aeruginosa is rare 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This includes discussing the importance of regular dental care and antimicrobial prophylaxis before procedures that may lead to bacteremia. Recommended prophylaxis for penicillin tolerant and penicillin allergic patients included Amoxicillin and Clindamycin, respectively [62].…”
Section: Endocarditis Prophylaxismentioning
confidence: 99%
“…Given the insidious presentation of prosthetic valves IE, it is worth mentioning that the high incidence of TAVR-IE after ViV-TAVR may also be attributed to unrecognized IE as the original cause of valve dysfunction. Conversely, post-TAVR moderate-severe aortic regurgitation is associated with a 2-fold increased risk of TAVR-IE [11], which is likely the consequence of high sheer stress from turbulent blood flow favoring the deposition of fibrin and the creation of a nidus for infection [25].…”
Section: Procedure-related Risk Factorsmentioning
confidence: 99%